2022
DOI: 10.48112/bcs.v1i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Study of Klebsiella Pneumoniae Isolated from Pneumoniae Infection Patients

Abstract: This study aimed for isolation and identification of Klebsiella pneumoniae was an opportunistic pathogen responsible for a wide range of clinical syndromes such as pneumonia in both hospital and community settings. Assessment some immune parameter this study was carried out in Al-Diwaniya Teaching Hospital in Al-Diwaniya Province during the period from December 2018 to February 2019. A total of 272 individuals in both sex: 139 males and 133 females, including 210 sputum and blood specimens were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Additionally, all recovered isolates were sensitive to amikacin, imipenem, and norfloxacin, likely due to their occasional use in the veterinary field in Egypt. This finding aligns with the results of Ali and Abu-Zaid [ 31 ], who reported 100% sensitivity to norfloxacin among K. pneumoniae isolates recovered from small ruminants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, all recovered isolates were sensitive to amikacin, imipenem, and norfloxacin, likely due to their occasional use in the veterinary field in Egypt. This finding aligns with the results of Ali and Abu-Zaid [ 31 ], who reported 100% sensitivity to norfloxacin among K. pneumoniae isolates recovered from small ruminants.…”
Section: Discussionsupporting
confidence: 92%
“…The results revealed an infection rate of 36% with K. pneumoniae in the studied animals. A previous study conducted in Egypt also reported a 36% infection rate of K. pneumoniae in pneumonic sheep and goats [ 31 ]. However, lower infection rates of 27.15% and 13.39% were reported in small ruminants with respiratory manifestations in Egypt [ 32 ] and Nigeria [ 33 ], respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Next, 5 mL wastewater was mixed with 5 mL buffered peptone water (BPW) media at a concentration of 2% (1:1) (Oxoid, UK) and incubated at 37°C for 24 h. Isolates obtained on BPW media were streaked on MacConkey agar (MCA) media (Oxoid) [17]. Pink and mucoid colonies suspected of being K. pneumoniae were subcultured on Eosin Methylene Blue Agar (EMBA) (Oxoid) and incubated at 37°C for 24 h [18,19]. Colonies on EMBA media were subjected to Gram-staining and IMViC tests.…”
Section: Isolation and Identification Of K Pneumoniaementioning
confidence: 99%
“…Klebsiella pneumoniae ferments lactose and reduces acid to produce pink colonies on MCA media. Klebsiella pneumoniae forms mucoid colonies on the media and has a large polysaccharide capsule [18]. Gram-stain results showed that the isolate was Gram-negative (Figure -2c) [29].…”
Section: Isolation and Identification Of K Pneumoniaementioning
confidence: 99%